Evaluation of quantitative dynamic contrast‐enhanced (DCE)‐MRI parameters using a reference region model in invasive ductal carcinoma (IDC) patients. Issue 1 (9th July 2020) - Li, Aijing; Pan, Yuning; Chen, Bin; Huang, Rong; Xia, Jianbi; Jin, Yinhua; Zheng, Jianjun
Abstract: In this study, we investigated the changes of quantitative dynamic contrast‐enhanced (DCE)‐MRI parameters using a reference region (RR) model for the breast invasive ductal carcinoma (IDC). We retrospectively analyzed 80 cases with pathologically confirmed IDC using quantitative DCE‐MRI with a RR model. The pharmacokinetic quantitative parameters and prognostic factors of IDC were measured, and the relationship between them was examined. The volume transfer constant (RRK trans ) and rate constant (Kep ) were significantly higher in patients with level 3 histological grading compared to patients with level 1 & 2 histological grading (p < 0.05), and patients with negative estrogen receptor (ER‐negative) and/or negative progesterone receptor (PR‐negative) compared to patients with ER‐positive (p < 0.05) and/or PR‐positive (p < 0.05), and Triple‐Negative Breast Cancer (TNBC) type compared to luminal type breast cancer, respectively. Our results demonstrated that high RRK trans and Kep values were associated with TNBC type. In addition, RRK trans and Kep parameters can differentiate luminal type and TNBC type breast cancer.